Should we risk it? : exploring environmental, health, and technological problem solving - Kammen, Daniel M., 1962-; Hassenzahl, David M. (Princeton : Princeton University Press, 1999)
"How dangerous is smoking? What are the risks of nuclear power or of climate change? What are the chances of dying on an airplane? More importantly, how do we use this information once we have it? The demand for risk analysts who are able to answer such questions has grown exponentially in recent years. Yet programs to train these analysts have not kept pace. In this book, Daniel Kammen and David Hassenzahl address that problem. They draw together, organize, and seek to unify previously disparate theories and methodologies connected with risk analysis for health, environmental, and technological problems. They also provide a rich variety of case studies and worked problems, meeting the growing need for an up-to-date book suitable for teaching and individual learning."--Jacket
1. Introduction -- 2. Basic Models and Risk Problems -- 3. Review of Statistics for Risk Analysis -- 4. Uncertainty, Monte Carlo Methods, and Bayesian Analysis -- 5. Toxicology -- 6. Epidemiology -- 7. Exposure Assessment -- 8. Technological Risk -- 9. Decision Making -- 10. Risk Perception and Communication -- App. A. Z-Scores -- App. B. Student's T-test -- App. C. Chi-Squared Distribution.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Environmental sciences -- Decision making; Environmental policy -- Government policy; Risk assessment; Health risk assessment; Technology -- Risk assessment; Science and state; Environmental health; Technology; Decision making; Environmental policy; Environmental Health; Technology; Risk Assessment; Public Policy; Decision Making; Health Status Indicators; Sciences de l'environnement -- Prise de décision.; Environnement -- Politique gouvernementale; Évaluation du risque; Risques pour la santé -- Évaluation.; Technologie -- Évaluation du risque; Politique scientifique et technique; Hygiène du milieu; Technologie; Prise de décision.; risk assessment; decision making; environmental policy; BUSINESS & ECONOMICS -- Infrastructure; SOCIAL SCIENCE -- General; Technology; Environmental health; Decision making; Environmental policy -- Government policy; Environmental sciences -- Decision making; Health risk assessment; Risk assessment; Science and state; Technology -- Risk assessment; Prise de décision.; Santé.; Évaluation du risque; Risicoanalyse; Besliskunde; Exacte wetenschappen; Geneeskunde; Technische wetenschappen; Évaluation du risque; Technologie -- Évaluation du risque; Risques pour la santé.; Politique de l'environnement -- États-Unis -- 20e siècle.; Politique scientifique -- États-Unis -- 20e siècle.